(untitled) (Hannover, Germany, 2008)
This book is structured into different sections. The first section covers diagnostic tools and provides a rational approach to common clinical problems. In the second section, diseases affecting each portion of the gastrointestinal tract are discussed in detail.
Keywords: Veterinary gastroenterology,Thú y tiêu hóa